Pyrolysis of shredded oil palm empty fruit bunches impregnated with cobalt catalyst / Rusmi Alias - Alias, Rusmi (Institute of Graduate Studies, UiTM, 2015)
The world community is concerned with the depletion of fossil fuel and looking at alternative energy resources such as biomass, solar, hydro and wind. With the growth of palm oil production in Malaysia, the amount of biomass residues generated also shows a corresponding increase. Currently, there are several routes being studied to convert the biomass to liquid bio oil, bio char and gases depending on the pyrolysis condition. Catalytic pyrolysis is proposed to be a viable technology to convert this biomass by having a catalyst introduced during the pyrolysis process and in contact physically with the biomass, in the formation of higher quality bio oil. The first goal of this thesis is to analyse the possibility of shredded oil palm empty fruit bunches (SOPEFB) as a catalyst support/carrier by direct impregnation method using cobalt as the catalyst. The concentration of the cobalt aqueous solution were prepared for 5,10,15 and 20 wt% and the SOPEFB samples were soaked in these solutions with the different soaking time. The functional groups that are involve in the reaction such as ion exchange and adsorption, leading to metal uptake by the SOPEFB. Results show that the sorption equilibrium is achieved approximately after 24 hours. The adsorption capacity was 8.12, 9.27, 11.16 and 12.06 mg/g of SOPEFB for the 5, 10, 15 and 20 wt% of cobalt aqueous solutions respectively...